2019
DOI: 10.1111/een.12755
|View full text |Cite
|
Sign up to set email alerts
|

Comparative responses of termite functional and taxonomic diversity to land‐use change

Abstract: 1. While it is clear that land‐use change significantly impacts the taxonomic dimension of soil biodiversity, how the functional dimension responds to land‐use change is less well understood. 2. This study examined how the transformation of primary forests into rubber tree monocultures impacts individual termite species and how this change is reflected in termite taxonomic and functional α‐diversity (within site) and β‐diversity (among sites). 3. Overall, individual species responded strongly to land‐use chang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 54 publications
2
11
0
Order By: Relevance
“… 28 In addition, termite morphological traits (such as leg length and mandible length) may also be affected by predation pressure and physical structure of the habitat floor since these traits are related to foraging behavior and defense. 29 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 28 In addition, termite morphological traits (such as leg length and mandible length) may also be affected by predation pressure and physical structure of the habitat floor since these traits are related to foraging behavior and defense. 29 …”
Section: Discussionmentioning
confidence: 99%
“…To generate a dataset of termite species richness across the globe, we aggregated data on termite species distributions and inventories of species richness. We combined inventory data based on datasets from Li et al., 30 , 31 Liu et al., 29 Cerezer et al., 16 termite database records ( https://www.termitediversity.org/ ) and GBIF records ( https://doi.org/10.15468/dl.yd4edv ) which included over 148151 additional records, almost entirely collated since 2000. After removing any duplicate records (same species at same latitude and longitude) this provided a total dataset of 2503 inventories, with a reasonable coverage across most termite-occupied parts of the planet.…”
Section: Methodsmentioning
confidence: 99%
“…Additive diversity partitioning of species richness and Simpson diversity showed that α component contributed 98.3% and 99.1% of the total diversity, respectively; an indication that most species were similar within fields in the two Counties. The low beta diversity within each county may be an indication of lack of significant differences in microhabitats which resulted in homogenization of the termite communities ( Liu et al., 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies targeting arthropods have shown a reduction of species richness (including local extinction) due to the replacement of natural ecosystems by intensively productive systems (Birkhofer et al, 2017; Rigal et al, 2018). However, functional diversity patterns are not clear: in some cases, trait richness decreases because of the habitat filtering process imposed by anthropogenic disturbance (Laliberte et al, 2010; Liu et al, 2019). In other cases, functional richness remains similar or increases, but the underlying mechanisms acting on the community assemblage are not well defined (Mayfield et al, 2005; Mouillot et al, 2013).…”
Section: Introductionmentioning
confidence: 99%